The effect of nutritional scores on mortality in COVID-19 patients - Aktan,Adem (2022)
SUMMARY OBJECTIVES: While studies on the treatment for the coronavirus disease 2019 (COVID-19) pandemic continue all over the world, factors that increase the risk of severe disease have also been the subject of research. Malnutrition has been considered an independent risk factor. Therefore, we aimed to investigate the clinical effect of dietary habits and evaluate the prognostic value of the Controlling Nutritional Status score in the COVID-19 patients we followed up. METHODS: A total of 2760 patients hospitalized for COVID-19 were examined. Patients were retrospectively screened from three different centers between September 1 and November 30, 2020. A total of 1488 (53.9%) patients who met the criteria were included in the study. Risk classifications were made according to the calculation methods of prognostic nutritional index and Controlling Nutritional Status scores and total scores. The primary outcome of the study was in-hospital mortality. RESULTS: The groups with severe Controlling Nutritional Status and prognostic nutritional index scores had a significantly higher mortality rate than those with mild scores. In the multivariable regression analysis performed to determine in-hospital mortality, the parameters, such as age (OR 1.04; 95%CI 1.02–1.06, p<0.001), admission oxygen saturation value (SaO2) (OR 0.85; 95%CI 0.83–0.87, p<0.001), and Controlling Nutritional Status score (OR 1.34; 95%CI 1.23–1.45, p<0.001), were independent predictors. The patient groups with a low Controlling Nutritional Status score had a higher rate of discharge with recovery (p<0.001). CONCLUSIONS: Higher Controlling Nutritional Status scores may be effective in determining in-hospital mortality in patients with COVID-19. Nutrition scores can be used as a useful and effective parameter to determine prognosis in patients with COVID-19.